1981
DOI: 10.1007/bf00376899
|View full text |Cite
|
Sign up to set email alerts
|

Contrasts in energy intake and expenditure in sit-and-wait and widely foraging lizards

Abstract: Daily energy metabolism and water flux were measured with doubly labeled water in the free-living insectivorous lizards Cnemidophorus tigris (mean body mass 15.7 g) and Callisaurus draconoides (8.6 g) in June 1979 in the Colorado Desert of California. C. tigris was an active forager; it spent 91% of its 5-h daily activity period in movement. C. draconoides was a sit-and-wait predator; it spent less than 2% of its 10-h activity period in movement. C. tigris had significantly higher rates of field energy metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
171
0
3

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(177 citation statements)
references
References 27 publications
3
171
0
3
Order By: Relevance
“…Second, the cost of locomotion during walking has been shown to be greater than running, both on a per stride basis and on an absolute basis, because WF actually spend the majority of their activity budget walking slowly (Anderson and Karasov, 1981;. Thus, it is difficult to support the idea that walking mechanics is a key adaptive innovation to reduce the metabolic cost of locomotion in WF.…”
Section: The Evolution Of Mechanics and Gait With Foraging Mode In LImentioning
confidence: 99%
“…Second, the cost of locomotion during walking has been shown to be greater than running, both on a per stride basis and on an absolute basis, because WF actually spend the majority of their activity budget walking slowly (Anderson and Karasov, 1981;. Thus, it is difficult to support the idea that walking mechanics is a key adaptive innovation to reduce the metabolic cost of locomotion in WF.…”
Section: The Evolution Of Mechanics and Gait With Foraging Mode In LImentioning
confidence: 99%
“…For example, an increase in proportion of fast-glycolytic fibers associated with high limb cycle frequency appears to enhance sprint speed in phrynosomatid species that locomote on sand (Bonine et al, 2001). Improved endurance capacity, involved in the large distances covered by lizards that forage actively, is associated with high proportions of oxidative fibers in the leg muscles (Mutungi, 1992), high field metabolic rates (Anderson and Karasov, 1981) and high metabolic scopes (Frappell et al, 2002). Muscle fibers of a glycolytic nature contract quickly but fatigue rapidly, whereas slow-oxidative fibers, aerobic in nature, exhibit high endurance (Brooks et al, 1996) but require improved oxygen delivery to the muscle.…”
Section: Tropidurid Lizards Have Colonized a Variety Of Brazilian Opementioning
confidence: 99%
“…The TRM for an ectothermic animal incorporates the energy expenditure of a resting animal with the daily body temperature pattern found in animals in the field (Anderson & Karasov 1981;Congdon & Tinkle 1982;Peterson, Nagy & Diamond 1990;Benabib & Congdon 1992). Although %AR is a more aggregated index than ECT, and therefore provides less detailed information about the subdivision of an animal's energy budget, it is easier to obtain because it does not require direct measurements of time, distance travelled and/or energy expended in locomotion.…”
Section: Introductionmentioning
confidence: 99%
“…The lizard studies that have subdivided the total daily energy expenditure into its components have demonstrated that widely foraging species have higher %ARs than sit-and-wait foragers (Anderson & Karasov 1981;Nagy, Huey & Bennett 1984) and that the proportion of energy used in activity (as well as the daily total) can change seasonally (Alexander & Whitford 1968;Merker & Nagy 1984;Christian & Tracy 1985;Mautz & Nagy 1987;Christian & Weavers 1994;Christian et al 1995;Christian, Griffiths & Bedford 1996a;Christian et al 1996b,c).…”
Section: Introductionmentioning
confidence: 99%